2021
DOI: 10.3390/f12121805
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Soil’s Chemical and Biochemical Properties Induced by Road Geometry in the Hyrcanian Temperate Forests

Abstract: Forest roads play an important role in providing access to forest resources. However, they can significantly impact the adjacent soil and vegetation. This study aimed to evaluate the effects of road geometry (RG) on the chemical and biochemical properties of adjacent soils to assist in environmentally friendly forest road planning in mountainous areas. Litter layer, canopy cover, soil organic carbon (SOC) stock, total nitrogen (TN), the activity of dehydrogenase (DHA), and urease (UA) enzymes at a 0–20 cm soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Cutting trees along the road reduces the incoming litter, which definitely affects the amount of organic matter in the soil. A significant increase in SOC and TN values at distances further from the road edge in the study of Rahbarisisakht et al (2021) was also observed. Soil nutrients, including available P and K, Ca and Mg, are typically reduced in roadside soils due to soil compaction.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Cutting trees along the road reduces the incoming litter, which definitely affects the amount of organic matter in the soil. A significant increase in SOC and TN values at distances further from the road edge in the study of Rahbarisisakht et al (2021) was also observed. Soil nutrients, including available P and K, Ca and Mg, are typically reduced in roadside soils due to soil compaction.…”
Section: Discussionmentioning
confidence: 58%
“…Based on the review of studies by other researchers, the maximum effective distance of the road on the environment in various studies is often up to 100 m in the forest (Avon et al 2010, Berenji Tehrani et al 2015, Deljouei et al 2018, Picchio et al 2018, Rahbarisisakht et al 2021). A 120 m buffer was created on the side of the excavation shoulder for inventory and collection of vegetation and soil data.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among other forestry infrastructure, forest roads are necessary for providing economical access to forest resources and services, representing an important component in forest management [7], [9], [30]. In order to facilitate the operations in areas managed for timber production, a well-developed network of roads is essential [2].…”
Section: Introductionmentioning
confidence: 99%